(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Stunting is a nutritional problem that causes impaired growth and development of children in Indonesia. Sukamanah Village is the priority locus for stunting in 2021 in Jatinunggal District. The implementation of this community service is to increase public knowledge about stunting and the fulfillment of complementary foods for breast milk with a demonstration of nutritious complementary feeding as an effort to prevent stunting. This community service activity was carried out in February 2022. The focus of this community service activity is to increase public awareness about stunting and its prevention efforts through the fulfillment of nutritious complementary foods. The community conducts a pre-test before providing counseling with the aim of knowing the description of community knowledge about stunting and complementary feeding. Counseling is carried out offline, including counseling about stunting and stunting prevention efforts including the fulfillment of complementary foods for breastfeeding for toddlers. The community returned to do a post-test after being given counseling with the aim of knowing the picture of community knowledge after being given counseling. The result is that after being given counseling, public knowledge about stunting and complementary feeding has increased. This activity went well and the community was very enthusiastic about listening to the counseling.